Case Report: A complete pathologic response in pancreatic cancer with squamous cell differentiation - Grant, Christopher R.; Arter, Zhaohui L.; Truc, Tran; Lee, Fa-Chyi (Frontiers in Oncology, 2023)
Primary pancreatic malignancies are mostly composed of the adenocarcinoma histological subtype. However, squamous cell carcinoma (SCC) accounts for approximately 0.5%–1% of all malignant pancreatic cancers. Because of the rarity of SCC of the pancreas, guideline-directed treatment is lacking, treatment response is difficult to access, and treatment options are poorly defined. Here, we report a case of a 65-year-old man diagnosed with pancreatic carcinoma with dominant squamous cell differentiation, who achieved complete pathologic response (CPR) after treatment with gemcitabine, cisplatin, and nab-paclitaxel every 14 days for six cycles and who continues to lead a high quality of life 7 months later. To our knowledge, this is the first case of CPR in a case of SCC of the pancreas. To highlight the ambiguity and the need for further studies, we also performed a narrative review analyzing recent cases and compared them to our case.